Characterization and Separation Performance of a Novel Polyethersulfone Membrane Blended with Acacia Gum. Issue 1 (December 2017) - Manawi, Yehia; Kochkodan, Viktor; Mahmoudi, Ebrahim; Johnson, Daniel; Mohammad, Abdul; Atieh, Muataz
Abstract Novel polyethersulfone (PES) membranes blended with 0.1–3.0 wt. % of Acacia gum (AG) as a pore-former and antifouling agent were fabricated using phase inversion technique. The effect of AG on the pore-size, porosity, surface morphology, surface charge, hydrophilicity, and mechanical properties of PES/AG membranes was studied by scanning electron microscopy (SEM), Raman spectroscopy, contact angle and zeta potential measurements. The antifouling -properties of PES/AG membranes were evaluated usingEscherichia coli bacteria and bovine serum albumine (BSA). The use of AG as an additive to PES membranes was found to increase the surface charge, hydrophilicity (by 20%), porosity (by 77%) and permeate flux (by about 130%). Moreover, PES/AG membranes demonstrated higher antifouling and tensile stress (by 31%) when compared to pure PES membranes. It was shown that the prepared PES/AG membranes efficiently removed lead ions from aqueous solutions. Both the sieving mechanism of the membrane and chelation of lead with AG macromolecules incorporated in the membrane matrix contributed to lead removal. The obtained results indicated that AG can be used as a novel pore-former, hydrophilizing and antifouling agent, as well as an enhancer to the mechanical and rejection properties of the PES membranes.